Epitaxial Growth of Main Group Monoelemental 2D Materials. (2nd November 2020) - Zhou, Dechun; Li, Heping; Si, Nan; Li, Hui; Fuchs, Harald; Niu, Tianchao
Abstract: Since the discovery of graphene, 2D materials have attracted significant attention for their unique properties. Monoelemental 2D materials (ME2DMs) are of particular interest because of their superiority in synthetic exploration, excellent mobility, and wide range of band gaps over other 2D compounds. Substantial efforts are devoted to fabricate high‐quality materials through various substrates and reveal the growth mechanism at the atomic scale. In this review, the recent progress in the preparation of these ME2DMs is explored, the roles of different substrates is highlighted, and the challenges of and perspectives on their heterostructures is discussed. Abstract : Recent progress in molecular beam epitaxy of the main group monoelemental 2D materials is reviewed, with an emphasis on the scanning tunneling microscopy characterization of their electronic and atomic structures. A range of substrate effects on phase engineering and growth mode are explored. By identifying current challenges and opportunities, a roadmap for heterostructures and binary 2D systems is provided.